2021
DOI: 10.3892/mmr.2021.12493
|View full text |Cite
|
Sign up to set email alerts
|

miR‑302d‑3p regulates the viability, migration and apoptosis of breast cancer cells through regulating the TMBIM6‑mediated ERK signaling pathway

Abstract: MicroRNAs (miRs/miRNAs) play important roles in the occurrence, metastasis and prognosis of multiple types of cancers. However, the specific role of miR-302d-3p and its underlying mechanism in breast cancer (BC) have not yet been reported. The present study aimed to identify the role of miR-302D-3p in BC and its potential mechanism using BC cell lines MCF7 and MDA-MB-231 and normal breast epithelial cell MCF-10A. Cancer and paracancerous tissue from patients with BC were also used. Reverse transcription-quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
(13 reference statements)
2
9
0
Order By: Relevance
“…In cancers, TMBIM6 is regarded as a promoter of cancer progression. For example, TMBIM6 regulates the extracellular signal-regulated kinase (ERK) pathway to promote the proliferation and migration of breast cancer cells ( 46 ). Another study reveals that TMBIM6 enhances proliferation and metastasis in non-small cell lung cancer cells ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…In cancers, TMBIM6 is regarded as a promoter of cancer progression. For example, TMBIM6 regulates the extracellular signal-regulated kinase (ERK) pathway to promote the proliferation and migration of breast cancer cells ( 46 ). Another study reveals that TMBIM6 enhances proliferation and metastasis in non-small cell lung cancer cells ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…40 Furthermore, miR-302d-3p-mediated regulation of TMBIM6 has been implicated in breast cancer cell viability, migration, and apoptosis, highlighting the potential therapeutic implications of targeting TMBIM6 and its associated downstream signaling pathways. 41 These findings collectively underscore the significance of TMBIM6 in cancer progression and advocate for its potential util- Targeting immune pathways associated with the recruitment and functionality of macrophages may represent a compelling therapeutic approach for improving outcomes in SKCM patients. Tumor-associated macrophages (TAMs) have emerged as a promising therapeutic target in the management of melanoma.…”
Section: Discussionmentioning
confidence: 84%
“…TMBIM6, also named as transmembrane Bax inhibitor motif containing-6, is an inhibitor of Bax-induced apoptosis [48]. Growing evidences has indicated that TMBIM6 exert an oncogenic role in multiple cancers, including squamous cervical, non-small cell lung, breast, nasopharyngeal, hepatocellular, glioblastoma, and laryngeal squamous cell carcinoma [29,37,45,[49][50][51][52][53]. Our study implied that TMBIM6 was modified by m6A in the transcription level and interacts with IGF2BP3 and STRIP2, resulting in the stabilization of TMBIM6.…”
Section: Discussionmentioning
confidence: 99%